(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2019)
Traditionally, documentary filmmaking has been both a tremendously complex and problematic cinematic practice, since it is based on presenting the “historical world” but at the same time, it has appealed to some different fictional strategies. Thus, this paper addresses the fictional strategies used in three contemporary documentaries: The Blonds, Waltz with Bashir, and The Missing Picture. The hypothesis states that recognition of the fragmentation of subjectivity and the fragility of memory make necessary the inclusion of diverse fictional strategies such as playing with viewers’ expectations, the use of moving images and the multiple disjunctions among voice, image and authorship.